Estimasi Trip Frequency Dengan Menggunakan Model Multiple Linear Regression - Chandra, Agung (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2017)
One important step in transportation planning is trip generation or trip frequency (trip production). Factors that influence trip frequency are income, family size, and vehicle ownership. One has to know the relationship between trip frequency and its factors by building the statistical model. The model is Multiple Linier Regression which the dependent variable is trip frequency and the independent variables are income, family size and vehicle ownership.